A gift of God in due season : essays on scripture and community in honor of James A. Sanders - Sanders, James A. (James Alvin), 1927-2020; Carr, David McLain, 1961-; Weis, Richard D. (Journal for the study of the Old Testament. Supplement series ;, 1996)
This volume of essays addresses from a variety of vantage points the relation of scriptures and community that has been so central to the canonical critical work of James A. Sanders. The first part of the volume focuses on the formation of the Jewish and Christian canons and texts in them, while the second part looks at ancient and modern appropriations of canonical texts. Together these essays show the multiple potential links between canonical criticism and historical, literary, feminist and other approaches in contemporary biblical studies.